2016
DOI: 10.1097/mjt.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Controversial Effects of Exogenous Testosterone on Cardiovascular Diseases

Abstract: The use of testosterone (T) among men aged 40 years or older was increased more than 3 times from 0.81% in 2001 to 2.91% in 2011. Until recently, the majority of the studies did not show any increased cardiovascular (CV) risk by using T in male patients with hypogonadism. What is more, some studies had observed a protective effect of using T against CV diseases. However, in 2010, a randomized clinical trial (RCT) was intended to study the advantage of T gel in older men with limitations in mobility; the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…As such, we examine the role of endogenous testosterone in patients without PrCa, the role of endogenous testosterone in PrCa patients, and the potential oncologic risks of exogenous testosterone from TRT in PrCa patients. Other aspects of TRT, including the potential benefits to hypogonadal men and risk of adverse cardiovascular effects are beyond the scope of our review and have been expertly reviewed elsewhere [Swerdloff and Wang, 2011;Spitzer et al 2013;Miner et al 2014;Al-Khazaali et al 2015;Morgentaler and Conners, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…As such, we examine the role of endogenous testosterone in patients without PrCa, the role of endogenous testosterone in PrCa patients, and the potential oncologic risks of exogenous testosterone from TRT in PrCa patients. Other aspects of TRT, including the potential benefits to hypogonadal men and risk of adverse cardiovascular effects are beyond the scope of our review and have been expertly reviewed elsewhere [Swerdloff and Wang, 2011;Spitzer et al 2013;Miner et al 2014;Al-Khazaali et al 2015;Morgentaler and Conners, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…57 In contrast to previous studies, some issues have raised concerning the cardiovascular safety of exogenous T therapy, especially in older men. 58 ADT is frequently used in the combination method for the therapy of prostate cancer and then can raise mortality from cardiovascular events. It was suggested that cardiometabolic risk due to ADT can be decreased by diet and lifestyle modification.…”
Section: Androgens In Cmsmentioning
confidence: 99%
“…However, with endocrinotherapy being used extensively, relevant side effects are also paid more attention by clinicians gradually. Endocrinotherapy can induce a serious of metabolic changes, such as obesity, hypertension, atherosclerosis, type 2 diabetes mellitus and osteoporosis (Al-Khazaali et al, 2015), in which the perniciousness of cardiovascular disease is the most serious. This study compared and analyzed the changes of blood indexes in patients with prostate cancer before and after treatment as well as incidence of cardiovascular disease in order to investigate whether aspirin could prevent the occurrence of cardiovascular disease in prostate cancer after endocrinotherapy, hoping to provide a certain evidences for clinical administration.…”
Section: Preventive Effects Of Aspirin On Cardiovascular Complications In Prostate Cancer Cases After Endocrinotherapymentioning
confidence: 99%